The relationship between kinesthetic perception of some kinematic variables and the accuracy of the crushing knocking skill in volleyball - بن يوسف, دحو (sports creativity, 2025)
The research aims to know the relationship between sensory-kinematic perception of some kinematic variables with the precision of overwhelming multiplication skill in volleyball,. A sample of (25) players out of (50) players from some school sport teams specializing in volleyball, Sensory-kinetic perception tests were used for the kinematic variables and the accuracy test for overwhelming multiplication skill. To analyze the results, the researcher used the Pearson correlation coefficient to measure the correlation significance and the simple regression coefficient to extract the prediction equations. Overwhelming hitting skill, kinesthetic perception tests, corners angles and distance variable, and direct correlation with time.